Penerapan Metode Principal Component Analysis (Studi Kasus: Tingkat Kemiskinan di Kepulauan Maluku) - Lesnussa, Trifena Punana; Utubira, Everd Elseos Martin; Kaseside, Meidy (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The Maluku Islands are a high-poverty region in Indonesia. The region consists of 2 provinces, namely Maluku province and North Maluku province. There are 21 districts/cities in the region, with 17 regencies and 4 municipalities. The poverty rate in this region is a challenge that always wants to be studied with a socio-population approach and a mathematical statistics approach. One method or approach in analyzing poverty is Principal Component Analysis (PCA). PCA has the advantage of simplifying information from various variables to several principal components without losing much information and can overcome the problem of multiple linearity by changing variables that correlate with freely related components. The purpose of this research is to identify poverty in districts/municipalities in Maluku Islands using the PCA approach. The results showed that the components formed by the PCA method were formed in 2 factors. Factor 1 consists of GRDP (X2), Life Expectancy Rate (X3), Unemployment Rate (X4) and Percentage of Population (X6). Meanwhile, factor 2 consists of 2 variables, namely the Poverty Level (X1) and TPAK (X5).